Effectiveness of Brainwave Music Therapy in Hypertensive Elderly with Sleep Disorders - Wahyuni, Eko Sari; Septyasih, Rossyana; Prastiwi, Swito; Abiddin, Andi Hayyun (Health Gate, 2024)
Elderly people who experience sleep disorders are at risk of various health problems, including hypertension. To treat insomnia comprehensively, an approach that not only relies on medication is needed, but also complementary therapies, one of which is brainwave music therapy. This music therapy can stimulate the brain to follow the vibrations and rhythms of music when individuals are in a resting state, so as to bring them into a relaxed state and make it easier to fall asleep. This study aims to analyse the effect of brainwave music therapy on the level of insomnia in elderly hypertension. The research design used a descriptive case study approach involving two hypertensive elderly subjects who experienced sleep disorders. Music therapy was performed six times with a duration of 10-15 minutes. Data were collected through insomnia scale and observation. The results showed a decrease in the level of insomnia in both subjects after undergoing brainwave music therapy. Subjects who initially experienced severe insomnia decreased to mild insomnia. This indicates that brainwave music therapy has the potential to be an effective non-pharmacological intervention in reducing insomnia symptoms in hypertensive elderly